Simulation and optimization of the perovskite solar cells - Liu, Xun (Nanyang Technological University, 2021)
In recent years, perovskite-based solar cell technologies have prompted a strong interest in scientific studies because of their multiple advantages such as low costs, lightweight, and ability to react to a different wavelength of sunlight. The current highest power conversion efficiency (PCE) of a perovskite solar cell is 25.5 percent, however, higher PCE and long-term stability can be further improved. As a result, the goal of this project is to model and improve the perovskite solar cell structure to increase its PCE. By using the GPVDM software, all five layers will be simulated, and then different thicknesses and materials of each layer will be compared, resulting in an optimum device. Based on simulation data, an optimal Perovskite Solar Cell structure is suggested in this project, which produces a PCE of 27.63 percent. In this project, I optimized each of the five layers of perovskite solar cells by simulating different thicknesses and materials. A high fill factor of 0.86 a.u is achieved, resulting in a high PCE of 27.63 percent.